Analisis Kinerja Keuangan Pemerintah Daerah: Studi Kasus di Kabupaten Tegal Periode 2016-2019 - Markus Rivaldo Yulinchton; Maria Bernadette Nani Ariani; Nunuk Triwahyuningtyas (Universitas Proklamasi 45, 2022)
This study aims to obtain the level of financial performance of the Government of Tegal Regency, Central Java Province. The sample used is the 2016-2019 Tegal Regency Budget Realization Report. The analysis technique used uses five different ratios, namely the ratio of regional financial independence, effectiveness ratio, growth ratio, harmony ratio, and fiscal decentralization ratio. The data collection technique was carried out by taking the data on the BPS (Central Bureau of Statistics) Tegal Regency website. The results show that the ratio of regional financial independence in the regional financial statements of Tegal Regency has an instructive pattern, while the effectiveness ratio is in the ineffective area. Other results show that the growth ratio is fluctuating, the compatibility ratio is in an unbalanced condition, and the ratio of fiscal decentralization is in a low category.